Cancer patients with neutropenic septic shock: etiology and antimicrobial resistance - Sung Min Jung; Youn Jung Kim; Seung Mok Ryoo; Chang Hwan Sohn; Dong Woo Seo; Kyoung Soo Lim; Won Young Kim (The Korean Journal of Internal Medicine, 2020)
Background/Aims Among patients with febrile neutropenia that developed after chemotherapy, high-risk patients, such as those having clinical instability or Multinational Association of Supportive Care in Cancer score of < 21, require hospitalization for intravenous empiric antibiotic therapy. Monotherapy with an anti-pseudomonal ß-lactam agent is recommended. Although many studies reported the microbial etiology of infections and resistant patterns of febrile neutropenia, the patients were not well characterized as having neutropenic septic shock. Therefore, this study aimed to determine the microbial spectrum of infections and resistance patterns of their isolates in patients with chemotherapy-induced neutropenic septic shock. Methods Data of adult patients diagnosed with neutropenic septic shock in the emergency department between June 2012 and December 2016 were extracted from a prospectively compiled septic shock registry at a single academic medical center. Thereafter, microbiological studies and antimicrobial susceptibility tests were conducted. Results In total, 109 bacteria were found in patients with neutropenic septic shock. Gram-negative bacteria were the predominant causative organisms (84, 77.1%). Moreover, 33 microorganisms (30.3%) were multidrug-resistant (MDR) bacteria with extended-spectrum ß-lactamase-producing Escherichia coli (17, 50%) being the commonest. The most commonly affected sites in patients with MDR bacterial infections were the gastrointestinal tract (45%) and unknown (43.5%). Approximately 48.5% of MDR bacteria were resistant to cefepime but not to piperacillin- tazobactam or carbapenem. Conclusions MDR bacteria were prevalent in patients with chemotherapy-induced neutropenic septic shock. Therefore, piperacillin-tazobactam or carbapenem may be considered as empiric antibiotics if MDR bacteria are suspected to be causative agents.